Family-based exome sequencing combined with linkage analyses identifies rare susceptibility variants of MUC4 for gastric cancer - Choi, Yoon Jin; Ohn, Jung Hun; Kim, Nayoung; Kim, Wonji; Park, Kyungtaek; Won, Sungho; Sael, Lee; Shin, Cheol Min; Lee, Sun Min; Lee, Sejoon; An, Hyun Joo; Jang, Dong Man; et al. (PLoS ONE, 2020)
Genome-wide association studies of gastric cancer (GC) cases have revealed common gastric cancer susceptibility loci with low effect size. We investigated rare variants with high effect size via whole-exome sequencing (WES) of subjects with familial clustering of gastric cancer. WES of DNAs from the blood of 19 gastric cancer patients and 36 unaffected family members from 14 families with two or more gastric cancer patients were tested. Linkage analysis combined with association tests were performed using Pedigree Variant Annotation, Analysis, and Search Tool (pVAAST) software. Based on the logarithm of odds (LOD) and permutation-based composite likelihood ratio test (CLRT) from pVAAST, MUC4 was identified as a predisposing gene (LOD P-value = 1.9×10-5; permutation-based P-value of CLRT ≤ 9.9×10-9). In a larger cohort consisting of 597 GC patients and 9,759 healthy controls genotyped with SNP array, we discovered common variants in MUC4 regions (rs148735556, rs11717039, and rs547775645) significantly associated with GC supporting the association of MUC4 with gastric cancer. And the MUC4 variants were found in higher frequency in The Cancer Genome Atlas Study (TCGA) germline samples of patients with multiple cancer types. Immunohistochemistry indicated that MUC4 was downregulated in the noncancerous gastric mucosa of subjects with MUC4 germline missense variants, suggesting that loss of the protective function of MUC4 predisposes an individual to gastric cancer. Rare variants in MUC4 can be novel gastric cancer susceptibility loci in Koreans possessing the familial clustering of gastric cancer. Copyright:
Keywords: Cohort Studies; Family; Female; Genetic Linkage; Genetic Predisposition to Disease; Genetic Variation; Germ Cells; Humans; Male; Middle Aged; Mucin-4; Pedigree; Reproducibility of Results; Stomach; Stomach Neoplasms; Whole Exome Sequencing